Incidence of knee chondrocalcinosis and its risk factors in a community‐based cohort. (2nd July 2018) - Cho, Nam H.; Song, Yoonah; Lee, Seunghun; Sung, Yoon‐Kyoung; Jun, Jae‐Bum
Abstract: Aim: Chondrocalcinosis results from deposition of calcium pyrophosphate dihydrate in articular cartilage. It is a relatively common radiographic finding of the joints, especially the knee. This study investigated the incidence and the risk factors for the development of knee chondrocalcinosis in the general population. Method: We used a prospective, ongoing cohort, composed of 5018 people, which was established in 2001 to investigate the epidemiologic characteristics of major chronic diseases in the Republic of Korea. The incidence of knee chondrocalcinosis was assessed per 1000 person‐years, and the risk factors were explored by Cox proportional hazard regression analyses. Results: A total of 4543 patients who did not have knee chondrocalcinosis at enrollment, year 2001–2002, were evaluated with a mean follow‐up duration of 8.4 ± 4.2 years. The crude incidence of knee chondrocalcinosis was 3.19 per 1000 person‐years (women, 3.55; men, 2.70), and the whole cumulative incidence of knee chondrocalcinosis was 2.7%. Older age (> 55 years) and higher HbA1C were associated with increased risk of knee chondrocalcinosis. Conclusion: This is the first study to report the incidence of knee chondrocalcinosis in the general population of Korea. Older age and high HbA1C were independent risk factors for development of knee chondrocalcinosis.